Evaluation of microbiological purity of nasal ointment "Mnemastym" - Al Nukari Abdulkarim; О. S. Koshelev; A. L. Drozdov (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2018)
The aim of this work was the determination of microbiological purity of nasal ointment “Mnemastym” with arginine-vasopressin (AVP).